Evaluation of Speaking Competence in Arabic Language Learning: A Performance Assessment Approach - Ahmad Fauzi; Siti Rahmawati (IJAS: International Journal of Arabic Studies, 2025)
Assessing Arabic speaking competence requires an evaluation method that accurately reflects students’ communicative abilities. This study examines the effectiveness of performance-based assessment in evaluating Arabic-speaking skills, focusing on fluency, coherence, accuracy, pronunciation, and confidence. Using a qualitative research design with thematic analysis, data were collected through structured speaking tasks, rubric-based assessments, observations, and interviews. The findings indicate that performance assessment provides a more comprehensive and authentic evaluation of speaking proficiency compared to traditional methods. Students who engaged in interactive speaking activities demonstrated higher fluency and coherence, while pronunciation challenges were primarily linked to phonemes unique to Arabic. Additionally, language anxiety was found to hinder speaking performance, emphasizing the importance of confidence-building strategies. The study highlights the advantages of performance assessment, particularly in offering detailed formative feedback and fostering intrinsic motivation among learners. These findings suggest that integrating performance-based evaluation into Arabic language instruction can enhance speaking proficiency and create a more effective learning environment. Future research should explore the implementation of digital tools in performance assessment and examine its long-term impact on Arabic language acquisition.